The Role of Gut Microbiota in Orthopedic Surgery: A Systematic Review - Nadeem-Tariq, Ahmed; Kazemeini, Sarah; Michelberger, Matthew; Fang, Christopher; Maitra, Sukanta; Nelson, Karen (Microorganisms (Basel), 2025)
The human gut microbiome represents a complex ecosystem comprising numerous microorganisms critical to basic physiological processes. The gut microbiome’s composition and functionality influence surgical outcomes following orthopedic procedures. The purpose of this study was to evaluate the gut microbiota on critical aspects of orthopedic surgical outcomes. A comprehensive literature search was conducted via PubMed, the Cumulative Index for Nursing and Allied Health Literature (CINAHL), Google Scholar, Cochrane Library, Medline, and Web of Science. A total of 18 research articles of the 599 retrieved results were included in this study. Significant correlations were identified between microbial composition and surgical outcomes, including infection rates, inflammatory responses, and postoperative complications. Bacterial genera like Alistipes and Helicobacter increased postoperative cognitive dysfunction (POCD) risk, while short-chain fatty acid (SCFA)-producing bacteria showed negative correlations with inflammatory markers. Probiotic interventions reduced POCD incidence from 16.4% to 5.1% and modulated inflammatory responses. Additionally, bacterial composition was associated with critical surgical parameters such as bone healing, infection rate, and recovery trajectory. Inflammation, healing processes, and recovery trajectories are influenced by microbial composition in surgical settings. Targeted interventions, such as probiotics, show promise in reducing surgical risks and improving patient recovery.